Assessing sustainability education in a transdisciplinary undergraduate course focused on real-world problem solving: a case for disciplinary grounding - Remington, Sonya M.; Hiller Connell, Kim Y.; Armstrong, Cosette M.; Musgrove, Sheryl (My University, 2013)
Purpose – University sustainability programs intend to provide an integrated education that fosters the key competencies that students need to solve real-world sustainability problems. Translating these key competencies into pedagogical practice in integrated academic programs is not straightforward and the effectiveness of certain teaching methods in fostering sustainability competencies is largely unknown. The purpose of this paper is to present the results of a classroom assessment aimed at determining the extent to which key sustainability competencies develop in students during an introductory transdisciplinary sustainability course. Design/methodology/approach – The paper summarizes three previously identified key sustainability competencies and describes teaching methodologies used in the introductory course described here to foster these competencies in students. The development of these competencies over the course of one semester is assessed using a pre-/post-test based on case analyses. The implications of these findings for academic sustainability programs are discussed. Findings – Based on the assessment used here, the sustainability competencies developed differently in students with different disciplinary affiliations as a result of the introductory sustainability course. Business majors did not improve any of the key competencies, Sustainability majors improved systems thinking competence only, and Sustainability minors who were majoring in another traditional discipline improved all competencies. Practical implications -- Universities incorporate sustainability into their undergraduate curricula in many ways, ranging from infusing sustainability into courses based in traditional disciplines to creating academic programs focused entirely on sustainability that offer stand-alone sustainability courses. The results of this assessment suggest that universities should pay attention to the different preconceptions and disciplinary affiliations of students, as well as the overall structure of their undergraduate curriculum, as they figure out how to make sustainability part of undergraduate education. Originality/value – The paper contributes to undergraduate sustainability education by shedding light on how sustainability might best be incorporated into specific academic programs. This information may help create more effective sustainability courses and academic programs, which may maintain the viability of current sustainability programs and promote the institutionalization of sustainability in higher education in general.
Keywords: Sustainability education; Transdisciplinary; Sustainability competencies; Assessment